The place of omega-3 and omega-6 acids in supplementary treatment of inflammatory joint diseases - Brygida Kwiatkowska (Termedia Publishing House, 2020)
Eating habits have been analysed for years as a factor influencing the development of autoimmune diseases and susceptibility to infections. On the basis of research, observational studies and meta-analyses, special attention was paid to omega-3 and omega-6 acids. The purpose of the review is to show the importance of omega-3 and omega-6 acids as important ingredients in the healthy diet and as factors protecting against the development of the most common inflammatory rheumatic diseases. The influence of these omega-3 and -6 acids on the course of rheumatic diseases and arguments for their use as complementary therapy are also presented.